MEWUJUDKAN PEMIMPIN AMANAH PADA PEMILU 2014 DALAM BINGKAI SEJARAH - Moh. Rosyid (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
Political parties serve as the wheel to realize that reliable national leader election is always interesting matter to be discussed. Optimism and pessimism toward the 2014 election color media coverage. For those who are optimistic, the existence of the institution of the Corruption Eradication Commission (KPK), free from ‘political interest’, and the Supreme Court (MA) support mass organizations such as NU and Muhammadiyah who criticize the state policy direction. There are also NGOs ‘contribution’ in guarding the performance of the government, and the power of the media as an element of the establishment of democracy. However, the result quality of 2014 parliamentary election is doubted by the public for: (1) candidates proposed by political parties are not selected based on competence, track record, and integrity, (2) the vision and mission of candidates are not well-publicized. Thus, their performance will be difficult to be evaluated once elected as a board member, (3) public control over the parliament is weaken, (4) the parties do not open up opportunities that enable them to adjudicate complaints concerning members of the parliament. Pros and cons in assessing the quality of the 2014 elections can be addressed to unravel tangled yarn. First, the cost of the general election needs to be simplified. Second, the state must allocates extra grant for the election to reduce the expense of elected candidates. Third, the rule of law is the key word.Keywords: identity, leaders, and law enforcement